Thermal management of moulds and dies : a contribution to improved design and manufacture of tooling for injection moulding - Moammer, A. A. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Industrial Engineering))--University of Stellenbosch, 2011.